Use of Six Planting Media on Shallow Bed and Plant Container Systems to The Growth and Yield of Sweet Potato (Ipomoea batatas L.) for Roof Garden - Sitawati Sitawati; Agus Suryanto; Euis Elih Nurlaelih (Research Journal of Life Science, 2017)
Roof garden is an alternative to overcome food security through breeding crops and horticultures of fruits and vegetables. The research was conducted in Malang by applying two planting systems, such as shallow bed (direct cropping) and plant container bag by the same planting medium treatments. Research, which applied shallow bed and container bag, was conducted using Randomized Block Design (RBD) by 6 treatments of planting medium and 4 replications, such as : Soil (100%) (M0), Soil + Charcoal (1:1) (M1), Soil + Cocopeat (1:1) (M2), Soil + Compost (1:1) (M3), Soil + Manure (1:1) (M4), and Soil + Moss (1:1) (M5). Data analysis of the research used analysis of variance, and if any significant influence was found, it would be followed by the Least Significant Difference (LSD) at level 5%. And then, it would be followed by T-test as comparison between shallow bed system and container bag system. Parameters that being observed in the research included length of crop, leaf area, numbers of tuber, fresh weight of tuber, dry weight of tuber, and total dry weight of plants. Results of the research showed that the application of medium types of soil and manure (1:1) by shallow bed system on Roof Garden concept may increase numbers of tuber, fresh weight of tuber, dry weight of tuber, and dry weight of Sweet Potato (Ipomoea batatas L.) in comparison with the application of soil medium and manure (1:1) by plant container bag system.